THE EVOLUTION OF SUSTAINABLE HUMAN RESOURCE MANAGEMENT RESEARCH: A BIBLIOMETRIC REVIEW - Tati Sumarti Bisri; Ade Suhara; Munir Azhari; Hilda Yuliastuti; Nanny Mayasari; Achmad Harristhana Mauldfi Sastraatmadja (LPSDI Bina Patria, 2025)
Sustainable Human Resource Management (Sustainable HRM) has become a prominent topic in organizational research, driven by the increasing imperative to embed sustainability into corporate strategy and operations. This study employs a bibliometric approach to analyze the intellectual, geographical, and thematic progression of Sustainable HRM literature. A total of 229 articles published between 2005 and 2025 were retrieved from the Scopus database and analyzed using VOSviewer. The analysis includes author co-authorship, international collaboration, keyword co-occurrence, and temporal overlay visualization. The findings indicate a substantial growth in research output, with the United Kingdom, the United States, and India emerging as leading contributors. Author co-authorship mapping reveals influential clusters, notably around Jabbour CJC. Thematic analysis identifies five dominant clusters: green HRM, corporate social responsibility (CSR), employee well-being, strategic alignment, and workforce adaptability in the post-pandemic era. The overlay visualization highlights a chronological shift from foundational themes such as environmental sustainability toward emergent topics like digital transformation and organizational resilience. This study provides an integrative overview of the evolution of Sustainable HRM scholarship, identifies research gaps, and outlines directions for future inquiry. The findings offer both theoretical contributions and practical implications for aligning human resource strategies with long-term sustainability objectives